Supporting Students with Invisible Disabilities: A Scoping Review of Postsecondary Education for Students with Mental Illness or an Acquired Brain Injury. Issue 6 (1st November 2016) - Venville, Annie; Mealings, Margaret; Ennals, Priscilla; Oates, Jennifer; Fossey, Ellie; Douglas, Jacinta; Bigby, Christine
Abstract: Students with invisible disabilities such as mental illness or acquired brain injury (ABI) experience multiple barriers that reduce their likelihood of postsecondary course completion. The present study conducted a systematic search of research reporting interventions for students experiencing mental illness or ABI to participate in postsecondary education. Nine databases were searched and a framework for categorising interventions and outcomes was developed. Forty-two studies revealed that most interventions were focused at the individual student level aiming to support students to build skills, grow confidence, or compensate for challenges through educational adjustments. There was wide diversity in research approaches used and a dearth of rigorous research designs. This review offers a more consistent way to define interventions and outcomes to guide future research and facilitate more meaningful comparisons between studies. The impacts of specific interventions on students' attainment of qualifications and subsequent workforce participation need further investigation.